1985
DOI: 10.1038/jcbfm.1985.4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Calcium Antagonist Nimodipine on Local Cerebral Blood Flow and Metabolic Coupling

Abstract: Summary:The effects of a continuous infusion of the calcium antagonist nimodipine (1 j,Lg kg -1 min -1) on local CBF (LCBF) and local cerebral glucose utilisation (LCGU) were studied, using the quantitative autoradio graphic [14C]iodoantipyrine and [14C]2-deoxyglucose techniques in 34 anatomically discrete regions of the brain in lightly restrained, conscious rats. The infusion of ni modipine at this concentration produced only a small (8%) reduction in the MABP. The administration of ni modipine did not alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Several possible mechanisms suggest that such drugs ameliorate ischemic cerebral damage by affecting cerebral vasoconstriction, 518 platelet aggregation, 19 and neuronal membrane and mitochondrial functions. 20 Recent investigations into brain ischemia in several animal species 2 -4 -21 - 22 and stroke patients 23 -24 have shown that calcium entry blockers may improve cerebral blood flow and metabolism. Improvements in neurologic and neuropathologic outcomes have also been observed in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several possible mechanisms suggest that such drugs ameliorate ischemic cerebral damage by affecting cerebral vasoconstriction, 518 platelet aggregation, 19 and neuronal membrane and mitochondrial functions. 20 Recent investigations into brain ischemia in several animal species 2 -4 -21 - 22 and stroke patients 23 -24 have shown that calcium entry blockers may improve cerebral blood flow and metabolism. Improvements in neurologic and neuropathologic outcomes have also been observed in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…These data are derived from reanalysis of the CBF investigations of Mohamed et al (1985a). Only data from the hemisphere ipsilateral to MCA occlusion are shown.…”
Section: Effect Of Nimodipine On Lcbf After Mca Occlusionmentioning
confidence: 99%
“…The part of the increase in CBF produced by felodipine and nicardipine may be ex plained by the enhanced CMR02. However, the percent increases in CMR02 produced by felodipine and nicardipine were much smaller than those in CBF, indicating that the in crease in CBF produced by these drugs was mainly due to a direct vasodilating action on the cerebral blood vessels; if a substance in creases CBF through enhancement of the cerebral oxygen consumption, the percent increase in CBF would be equal to the percent increase in cerebral oxygen consumption (10,14).…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with the results of experiments conducted by d'Avella et al (13) in unanesthetized rats with nimodipine, another dihydropyridine calcium antagonist. Although Haws et al (12) and Mohamed et al (14) reported that nimodipine did not in crease CMRO2 or cerebral glucose uptake, their experiments were conducted in an esthetized animals. As a possible explanation for the enhancement of the cerebral metabolic rates, the elevation of cyclic AMP level due to inhibition of phosphodiesterase (15, 16) could be invoked, for it was known that intracarotid administration of cyclic AMP or intracisternal dibutyryl cyclic AMP could increase CBF, CMR02 and cerebral glucose consumption and reduce CVR in the baboon (17).…”
Section: Discussionmentioning
confidence: 99%